Leishmania (Viannia) DNA detection by PCR-RFLP and sequencing in free-ranging owl monkeys (Aotus azarai azarai) from Formosa, Argentina - Acardi, Soraya Alejandra (2013)
American Cutaneous Leishmaniasis (ACL) is caused by protozoan parasites of the Leishmania genus, and transmitted by females of the Phlebotominae family. The role of wild and domestic hosts in the cycle of Leishmania is still unknown. ACL is endemic in the province of Formosa where Nyssomyia neivai was the most abundant species in several captures and 31 cumulative ACL human cases were reported between 2005 and 2011 in the province. The present report describes the detection, by PCR-RFLP and confirmed by sequencing, of subgenus Leishmania (Viannia) DNA in four free-ranging owl monkeys (Aotus azarai azarai) from Formosa Province. The sequence amplified was the mini-exon gene present in tandem repeats in all species of the Leishmania genus from buffy coat samples. The absence of inhibitors in the samples was checked by a β-globin protocol originally designed to amplify the human β-globin gene. However, other free-ranging primates were found with natural infections of L. (V) braziliensis complex and Leishmania (Viannia) subgenus by parasitological means in America. To the best of our knowledge, there are no published reports on detection of subgenus Leishmania (Viannia) DNA by PCR-RFLP in argentinean free-ranging primates. Additional eco-epidemiological and parasitological studies are necessary to confirm owl monkeys, or any other natural infected mammal species detected by PCR, as a reservoir, incidental host or to propose it as an animal model for research on this topic.